Volume and correlates of objectively measured physical activity and sedentary time in non‐Hodgkin lymphoma survivors. Issue 2 (11th November 2015) - Boyle, Terry; Lynch, Brigid M.; Ransom, Emily K.; Vallance, Jeff K.
Abstract: Objectives: Few studies have measured the physical activity levels of non‐Hodgkin lymphoma (NHL) survivors, and no previous studies have measured sedentary behavior levels in this population. This study used accelerometers to measure the physical activity and sedentary time levels of NHL survivors and examined the demographic, behavioral, and medical correlates of these behaviors. Methods: A total of 156 NHL survivors (mean age = 64 years) completed a questionnaire and wore an accelerometer for seven consecutive days during waking hours. Descriptive statistics were used to describe physical activity and sedentary time levels, and linear regression was used to investigate correlates of these behaviors. Results: Participants averaged 8.6 h of sedentary time per day (60% of their accelerometer wear time), 5.3 h of light‐intensity physical activity (37%), and 30 min of moderate‐intensity physical activity (3%). Only 12% of the participants accrued the duration of moderate‐vigorous physical activity recommended by physical activity guidelines (30 min accrued in bouts of at least 10 min). Female participants, older participants, smokers, and participants with larger waist circumference had lower levels of moderate‐to‐vigorous intensity physical activity. Smokers and participants with larger waist circumference also had higher sedentary time levels. Conclusion: The NHL survivors in this study spent the majority of their waking hours sedentary, and few met physical activity guidelines. The results of this study emphasize the need for more research exploring the health consequences of sedentary behavior and physical inactivity in NHL survivors. Copyright © 2015 John Wiley & Sons, Ltd.